Teori Aset dalam Perspektif Fiqih Islam dan Pengembangan Industri Halal - M. Luthfillah Habibi; Kasuwi Saiban; Misbahul Munir (Tasharruf : Journal of Islamic Economics and Business, 2022)
An understanding of assets from a sharia perspective is very important in relation to the halal industry. This is because assets are the object of the transaction as well as one of the pillars of ta'aqud which is the majority of the Intiqolul Milkiyah method. By looking at the urgency of understanding assets from a sharia perspective, this study attempts to conduct a study of assets to produce a systematic asset description. The method used is a literature study. Excavation of this asset description refers to the Qur'an, Al Hadith and books of fiqh to obtain depth of analysis. Finally, this research formulates that haram products are divided into four, namely from the aspect of its essence, how to get it, where to get it and when to get it. In addition, this study also formulates that only assets that have sharia value can be transacted with syar'iyah contracts. And understanding fiqh in relation to the development of the halal industry will greatly help the growth and development of the halal industry in a massive, comprehensive and integrative manner.